A new discovery of a long-winged form of Mexican endemic grasshopper Melanotettix dibelonius Bruner, 1904 (Orthoptera: Acrididae: Gomphocerinae) and notes on wing polymorphism and geographic distribution - Mariño-Pérez, Ricardo; Sanabria-Urbán, Salomón; Foquet, Bert; Pocco, Martina E.; Song, Hojun (Zootaxa, 2020)
The species Melanotettix dibelonius Bruner, 1904 was previously recorded from Michoacán and Guerrero states in Mexico. This species is characterized by its tegmina, which are always shorter than head and pronotum together and sometimes shorter than the pronotum. After recent field expeditions (2015-2019) and an extensive review of museum specimens from the most important Orthoptera collections in Mexico and USA (291 specimens), we discovered a long-winged form of this species south of its previous known range, which effectively expanded its distribution range into Oaxaca state. We discuss some aspects regarding the patterns of geographic distribution and morphological variation among the long-winged and short-winged morphs. We conduct statistical analyses and observed that on average, the tegmina of long-winged individuals (both females and males) are slightly longer than twice the length of pronotum; whereas in short-winged individuals the tegmina are nearly as long or slightly longer than the length of the pronotum. Moreover, on average, females appear to have longer tegmina than males in both morphotypes. We provide photographic records of both forms live and mounted, the most comprehensive distribution map to date and a discussion of evolutionarily interesting patterns found in this species.